Research journey of sports promotion: A bibliometric analysis - Sofyan, Davi; Abdullah, Khairul Hafezad; Nurfadila, Frila; Tanucan, Jem Cloyd Melendres; Akinci, Abdullah Yavuz; Rojo, Jeferson Roberto (Universitas Padjadjaran, 2024)
Background: Research on exercise and health promotion has grown significantly, indicating an increasing interest in physical fitness and healthy living among people. Purpose: This study aimed to to provide a comprehensive overview of research on health and sports promotion, identify the field, identify prominent papers and academics, and use keyword analysis to determine the thematic focus. This research hoped to contribute to understanding the emerging dynamics in this interdisciplinary sector. Methods: Bibliometric methods analyse data sets that include publication trends, author information, countries, and newly discovered keywords. This analysis used VOSviewer bibliometric analysis software. The data analysed was 1,850 documents. Results: The results showed a steady increase in publications on sports, physical exercise, and health promotion issues. The reputable publications are those in the “International Journal of Environmental Research and Public Health” and “BMC Public Health”. Key phrases, such as “physical activity” and “health promotion” dominate the themes, with the United States and the United Kingdom emerging as important contributors. Conclusion: This study highlighted notable researchers, important sources, and concentrations of subjects in health and exercised promotion research, which underscored its dynamic nature. The knowledge gathered from this bibliometric research contributed to a more complex understanding of this interdisciplinary field’s changing goals and trends. Implications: Thematic concentration and identifying important articles can inspire evidence-based strategies for global health and physical activity promotion, international collaboration, and future research orientation.